Bevak Pintar: Taman Belajar Anak Merauke dalam Mengatasi Buta Aksara - Juli Arianti; Yohannes Putra Perkasa Sinambela; Najdah T; Riris Lawitta Maulina Siahaan; Prima Lestari Situmorang (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
Papua Province remains at the top in addressing illiteracy issues. The Community Literacy Development Index (IPLM) in Papua Province stands at 20.02, significantly lower than the national IPLM average of 64.48. In 2022, it was reported that the literacy rate among individuals aged 15–59 in Papua Province was 81.53%, indicating that nearly 20% of this age group in the province is still unable to read, write, or perform basic arithmetic. According to the head of the South Papua Province Education and Culture Office, over 36,252 children who should be attending primary to senior high school are either out of school or have dropped out. Merauke Regency contributes the highest numbers compared to other regencies. The purpose of this community service initiative is to provide literacy and numeracy (calistung) education to children who have dropped out or never attended school. The implementation method comprises three stages: planning, execution, and evaluation.The results of three months of calistung teaching at *Bevak Pintar* showed significant improvement in the reading, writing, and arithmetic skills of children who had dropped out of school or had never attended school.